(untitled) (Journal Of Educational and Psychological Researches, 2018)
The present research aims to measure the wisdom among university students and the differences of the concept of wisdom according to the gender of students in college of Basic Education. The sample of the research reached (300) male and female students in the morning studies upon the four stages of the psychological guidance department, the Scale of wisdom has been designed by the researcher herself and the psychometric feature were obtained as validity and Reliability. the researcher used Chi- square to Know the differences between the number of agreed and disagreed students for the wisdom scale, as well as the researcher used person correlation coefficient to Know the reliability of the scale by re test method for wisdom scale , t- test for one sample and t-test for two independent sample were used as well. The research reached the following results: 1. The sample of the research had a high level of wisdom generally. 2. There is a difference in regard of Gender (male- female) for the side of male. To conclude, the researcher came out with some Recommendations and suggestions for the research.